2007
DOI: 10.4049/jimmunol.178.7.4395
|View full text |Cite
|
Sign up to set email alerts
|

The Bxs6 Locus of BXSB Mice Is Sufficient for High-Level Expression of gp70 and the Production of gp70 Immune Complexes

Abstract: High levels of the retroviral envelope protein gp70 and gp70 immune complexes have been linked to a single locus on chromosome 13 (Bxs6) in the BXSB model, to which linkage of nephritis was also seen. Congenic lines containing the BXSB Bxs6 interval on a non-autoimmune C57BL/10 background were bred in the presence or absence of the BXSB Y chromosome autoimmune accelerator gene (Yaa), which accelerates disease in male mice. In these mice, we have shown that Bxs6 is sufficient to cause high-level expression of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 26 publications
(38 reference statements)
1
27
0
Order By: Relevance
“…It is significant that the Sgp3 locus also contributes to the production of anti-gp70 autoantibodies [32,91,92]. Moreover, we have recently observed that the production of gp70 IC was almost completely suppressed in B6.Nba2 mice deficient in TLR7 [98], indicating a critical role of TLR7 in the development of the antigp70 autoimmune response.…”
Section: Tlr7-dependent Implication Of Endogenous Retroviruses In Murmentioning
confidence: 96%
See 2 more Smart Citations
“…It is significant that the Sgp3 locus also contributes to the production of anti-gp70 autoantibodies [32,91,92]. Moreover, we have recently observed that the production of gp70 IC was almost completely suppressed in B6.Nba2 mice deficient in TLR7 [98], indicating a critical role of TLR7 in the development of the antigp70 autoimmune response.…”
Section: Tlr7-dependent Implication Of Endogenous Retroviruses In Murmentioning
confidence: 96%
“…Interval mapping of backcross progeny between lupus-prone mice and B6 or B10 mice identified a major locus controlling gp70 production in the middle of chromosome 13, designated Sgp3 or Bxs6 (the Bxs6 locus identified in BXSB mice is likely to be identical to Sgp3) [32,81,90,91]. Analysis of B6 or B10 mice congenic for the Sgp3 (or Bxs6) locus derived from either the NZB, NZW or BXSB strain revealed that all congenic mice had approximately 10-fold higher levels of gp70, as compared with wild-type B6 or B10 mice [32,91,92]. This suggested that the underlying allele of Sgp3 is shared among the three different lupusprone mice.…”
Section: Tlr7-dependent Implication Of Endogenous Retroviruses In Murmentioning
confidence: 97%
See 1 more Smart Citation
“…We have recently shown that the production of gp70 IC implicated in murine lupus nephritis was dependent on TLR7 [28, 43] and that the Sgp3 locus contributes to the development of anti-gp70 autoimmune responses [23]. Since it is unlikely that virion-free serum gp70 is able to trigger TLR7, Sgp3 could enhance the production of endogenous retroviral virions carrying singlestranded RNA, which would then promote the development of autoimmune responses against serum retroviral gp70 through the activation of TLR7.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism can sustain the production of IFN-α, thereby establishing a vicious cycle not only aggravating the autoimmune process but also promoting the development of autoimmune responses against a wide array of autoantigens that do not engage TLR7. Notably, endogenous retroviruses could elicit autoimmune responses against not only retroviral gp70 but also nuclear autoantigens in mice predisposed to SLE [49], and Sgp3 congenic mice produced significant titers of anti-DNA autoantibodies [22, 23]. …”
Section: Discussionmentioning
confidence: 99%